2006
DOI: 10.1021/bi052563z
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Phospholipase A2 from Arabidopsis thaliana:  Insights into the Three-Dimensional Structure and the Amino Acids Involved in Catalysis

Abstract: A low-molecular weight phospholipase A2 from Arabidopsis thaliana, isoform phospholipase A2-alpha, has been expressed in Escherichia coli in the form of inclusion bodies, refolded, and purified to homogeneity to yield the active mature enzyme. The enzyme was characterized with respect to pH, temperature optimum, and Ca2+ ion requirement. The enzyme has been shown to be a true secretory phospholipase A2 that requires Ca2+ ions in the millimolar range and belongs to group XIB. On the basis of the three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…This hypothesis is supported by our results showing that pollen germination was inhibited by manoalide and that this inhibition could be rescued by LPE but not by LPC or LPA (Figure 9). The low molecular weight PLA 2 s in plants have been classified as secreted PLA 2 s based entirely on their structural features, such as a large number of disulfide bonds, two antiparallel central helices, a catalytic His-Asp dyad, a hydrogen binding network between the interfacial binding site and the catalytic site, and a calcium binding loop (Berg et al, 2001;Lee et al, 2005;Mansfeld et al, 2006;Mansfeld, 2009). The results of a computer-based homology modeling analysis suggest that these plant sPLA 2 s are similar to those of sPLA 2 s from bovine pancreas and bee venom in terms of their tertiary structures of the active site and calcium binding loop (Mansfeld et al, 2006) In addition, a transient expression analysis of GFP in onion epidermal cells showed that PLA 2 -b and -g are secreted to the cell wall/extracellular space Lee et al, 2003).…”
Section: Pollen-expressed Pla 2 Members May Have a Preferential Role mentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by our results showing that pollen germination was inhibited by manoalide and that this inhibition could be rescued by LPE but not by LPC or LPA (Figure 9). The low molecular weight PLA 2 s in plants have been classified as secreted PLA 2 s based entirely on their structural features, such as a large number of disulfide bonds, two antiparallel central helices, a catalytic His-Asp dyad, a hydrogen binding network between the interfacial binding site and the catalytic site, and a calcium binding loop (Berg et al, 2001;Lee et al, 2005;Mansfeld et al, 2006;Mansfeld, 2009). The results of a computer-based homology modeling analysis suggest that these plant sPLA 2 s are similar to those of sPLA 2 s from bovine pancreas and bee venom in terms of their tertiary structures of the active site and calcium binding loop (Mansfeld et al, 2006) In addition, a transient expression analysis of GFP in onion epidermal cells showed that PLA 2 -b and -g are secreted to the cell wall/extracellular space Lee et al, 2003).…”
Section: Pollen-expressed Pla 2 Members May Have a Preferential Role mentioning
confidence: 99%
“…Contrary to the extracellular space, the ER and/ or Golgi provide the ideal environments for the PLA 2 s to carry out proper enzyme activity. Second, the head-group specificities of plant sPLA 2 s are quite different from those of animal sPLA 2 s. Most of the animal sPLA 2 s prefer anionic phospholipids, but plant enzymes have a preference for zwitterionic phospholipids, such as PE and PC (Mansfeld et al, 2006;Mansfeld and Ulbrich-Hofmann, 2007). According to Mansfeld (2009), these differences may be due to the evolutionary adaptation of plant PLA 2 specificity to the difference in the natural phospholipid composition between plants and animals.…”
Section: Pollen-expressed Pla 2 Members May Have a Preferential Role mentioning
confidence: 99%
“…Strong density is observed in both subunits for the Ca 2ϩ -bound water and for another that is bound to it. In subunit A, clear density is observed for a third, which interacts with the Ca 2ϩ -bound water, the side chains of His 61 and Asp 62 and the main-chain carbonyl of Cys 58 , whereas weak density suggests the presence of a fourth water molecule interacting only with the other waters. In subunit B the latter has strong density, whereas very little density is seen for the water coordinating His 61 , Asp 62 , and Cys 58 .…”
Section: Resultsmentioning
confidence: 99%
“…In subunit A, clear density is observed for a third, which interacts with the Ca 2ϩ -bound water, the side chains of His 61 and Asp 62 and the main-chain carbonyl of Cys 58 , whereas weak density suggests the presence of a fourth water molecule interacting only with the other waters. In subunit B the latter has strong density, whereas very little density is seen for the water coordinating His 61 , Asp 62 , and Cys 58 . The water at this position is interesting, because it corresponds to the proposed assisting water molecule, and its presence supports the water-assisted calcium-coordinate oxyanion mechanism of PLA 2 (15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of protein structures is generally 2 Journal of Viruses [13][14][15], theoretical models [16][17][18][19], and protein engineering [20,21]. For in silico ligand designing to be an effective inhibitor, Rep protein of selected begomovirus strains (YP 003288785, YP 002004579, and YP 003288773), which is responsible for replication, was used.…”
Section: Introductionmentioning
confidence: 99%